2019
DOI: 10.1250/ast.40.116
|View full text |Cite
|
Sign up to set email alerts
|

A polydimethylsiloxane-based axicon lens for focused ultrasonic brain stimulation techniques

Abstract: In this work, we built ultrasonic disc-shaped transducer for targeted neuromodulation with the addition of a solid axicon lens based on a polydimethylsiloxane (PDMS) interface. We made a numerical and experimental characterization of its acoustic field. The motor cortex of CF-1 mice was stimulated, through the skin and skull into the intact brain, with low-intensity pulsed ultrasound. Evoked muscle responses in different body segments were clearly observed, including hindlimb, forelimb, and tail. Axicon lens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…However, this loss of resolution is compensated by adequate stand-off of axicon lens. In addition, we find that the PDMS provides a smaller focal zone, which is desirable for neurostimulation [6]. All this allows a higher resolution, comparable to spherical transducers (the most commonly used for ultrasonic brain therapy), but with the advantage that the near field is eliminated, and the focus distance is shortened.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this loss of resolution is compensated by adequate stand-off of axicon lens. In addition, we find that the PDMS provides a smaller focal zone, which is desirable for neurostimulation [6]. All this allows a higher resolution, comparable to spherical transducers (the most commonly used for ultrasonic brain therapy), but with the advantage that the near field is eliminated, and the focus distance is shortened.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the implementation of ultrasound model with the k-Wave Toolbox was validated in our previous work [6] using experimental measurements of FUS made with the same axicon lens attached transducer and a needle hydrophone (Force Technology MH28) within a 6-L anechoic test tank. Our previous study has already shown that there is a good agreement between the simulated and experimental beam patterns.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Yeo et al [ 20 ] showed that PDMS can be used in the propagation of surface acoustic waves. A study by Acquaticci et al [ 21 ] showed that PDMS can be done on axicon lens for focusing ultrasonic brain stimulation techniques. Research by Romo-Uribe et al [ 22 ] showed that adding 10 wt.% of PDMS to epoxy resin can effectively improve the thermomechanical properties and toughness of epoxy resin.…”
Section: Introductionmentioning
confidence: 99%